Environmental Toxicology - Environmental Toxicology (Wiley, 2026)
Environmental Toxicology is a hybrid journal providing a forum to advance the scientific understanding of all aspects of environmental contaminants and their toxicological impacts on all living organisms. The journal provides a multidisciplinary platform for publishing innovative research, comprehensive reviews, and critical insights into the complex interactions between environmental pollution, and ecosystems.
FI 1.07
Q2
Keywords: Chemistry; Toxicology; Toxicología; Acuerdos transformativos; Transformative agreements; Toxicología ambiental y ecotoxicología; Contaminantes ambientales, exposición, riesgos para la salud y salud de ecosistemas; Evaluación y gestión de riesgos, mitigación y remediación de la contaminación